Use of zinc salts of DMTD in coating compositions
The use of DMTD zinc salt and lithium salts in coating compositions addresses the toxicity and corrosion resistance issues of chromium-based coatings by enhancing protective layer barrier function, achieving superior corrosion resistance measurable by EIS.
Patent Information
- Application Number
- JP2024541201
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-17
- Filing Date
- 2023-01-17
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-01-17
AI Technical Summary
Existing chromium-containing protective coatings for metal substrates are toxic and face challenges in meeting industrial corrosion resistance standards, necessitating the development of non-chromium alternatives with improved long-term corrosion resistance.
A coating composition incorporating a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD) and lithium salts, such as lithium carbonate, phosphate, bicarbonate, or oxalate, enhances the barrier function of protective layers on metal surfaces, using electrochemical impedance spectroscopy (EIS) to quantify the reinforcement.
The combination of DMTD zinc salt and lithium salts significantly improves the barrier function of protective layers, providing enhanced corrosion resistance that is visually unobservable but measurable through EIS, offering better and longer-term protection compared to individual components.
Smart Images

Figure 2025502127000016 
Figure 2025502127000017 
Figure 2025502127000001
Abstract
Description
[Technical field]
[0001] The present invention relates to the use of zinc salts of DMTD in coating compositions having protective properties, particularly useful for metal substrates. [Background technology]
[0002] Protective coatings are widely used to protect substrates, especially metal substrates, from corrosion. Hexavalent chromium compounds have long been used as corrosion inhibitors in protective coatings and conversion treatments of metal surfaces. However, hexavalent chromium is toxic and is therefore scheduled to be phased out for environmental, worker safety, and regulatory reasons. Although alternative chromium-free inhibitors have been proposed in recent years, many formulations struggle to meet the corrosion resistance standards, especially in industry.
[0003] Although much progress has been made in chromium substitution in corrosion protection coatings, it remains desirable to provide Cr-free coatings that have improved long-term corrosion resistance properties that are equivalent to or better than conventional Cr-containing coatings.
[0004] Recently, coating compositions with lithium salts have been proposed as an alternative to Cr-containing coatings. See, for example, "Chemical Properties of Coatings with Lithium Salts," IEEE Transactions on Materials Science and Engineering, Vol. 13, No. 1, pp. 1171-1175, 2002. As described in this paper, coating compositions with lithium salts have been demonstrated to have anticorrosive activity due to the formation of a protective layer on the substrate metal at locations where the coating deposited from the coating composition with lithium salt has defects. Such a layer was found to contain aluminum, oxygen and lithium that have leached from the coating. The protective layer provides a barrier between the metal surface at the coating defect and the corrosive environment. This barrier function and the strength of this protective layer may be important for long-term protection. Insufficient barrier function or low strength of the formed protective layer may result in localized metal defects and corrosion.
[0005] It is desirable to provide coating compositions that have improved barrier properties. [Prior art documents] [Non-patent literature]
[0006] Visser, P., Liu, Y., Terryn, H. et al. “Lithium salts as leachable corrosion inhibitors and potential replacement for hexavalent chromium in organic coatings for the protection of aluminum alloys” J Coat Technol Res 13, 557-566 (2016) Summary of the Invention
[0007] The inventors have found that when the coating composition also contains a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD), the protective layer formed on the coating defects by the action of the lithium salt exhibits significantly higher barrier function as observed by electrochemical impedance spectroscopy (EIS). The zinc salt of DMTD acts as an enhancer of the barrier function of the protective layer formed on the exposed metal surface.
[0008] The present invention therefore relates to the use of a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD), the zinc salt of DMTD being 2,5-dimercapto-1,3,4-thiadiazole zinc salt (VII), comprising the metal salt and a) a resin system comprising an organic film-forming resin and, optionally, a curing agent reactive with the organic film-forming resin; b) a lithium salt having a solubility in water in the range of 0.01 to 120 g / L at 20° C. selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate; In a coating composition further comprising To enhance the barrier function of a protective layer produced as a result of the presence of a lithium salt in a coating composition when used on a metal substrate coated with the coating composition; The use of the zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD) is provided. [Brief description of the drawings]
[0009] [Figure 1] 1 shows the results of EIS measurements of coating compositions according to some embodiments of the present invention. [Diagram 2] 1 shows the results of EIS measurements of coating compositions according to some embodiments of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Surprisingly, it has been found that the use of zinc salts of DMTD enhances the protective layer formed by lithium ions on the metal surface at coating defects when used with lithium salts selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate in the coating composition. The formation of a protective layer by lithium ions has previously been shown to be the mechanism of corrosion protection of lithium salts. When a coating defect forms in a cured coating, thus exposing the metal substrate and making it susceptible to corrosion, lithium ions leach from the coating to the metal surface and contribute to the formation of a protective layer at the surface. The presence of such a protective layer can be seen and its properties quantified using electrochemical impedance spectroscopy (EIS). See, e.g., "Electrochemical Properties of Coatings in a Metallic Coating," vol. 1, No. 1, pp. 1111-1115, 2002. This electrochemical method allows for the quantification of the barrier properties of the protective layer at the damaged area (scribe) created by the active protective mechanism (leaching) of the coating after exposure to accelerated corrosion tests (e.g., neutral salt spray exposure).
[0011] The magnitude of the barrier function is derived from the electrochemical impedance spectrum. The impedance modulus plot is the impedance modulus (Ω cm) as a function of frequency range (Hz). 2 ) The increase in impedance coefficient in the mid-frequency range 10 Hz can be related to the formation of a protective layer in the damaged area (scribe). The increase in impedance coefficient at low frequencies (10 mHz) can be related to the inhibition of corrosion processes at the substrate. An important advantage of using EIS is the ability to quantify differences between coating formulations that cannot be observed or quantified by visual methods.
[0012] The inventors have tested many compounds and found enhancing agents that enable the protective layer formed by the lithium salt to exhibit significantly higher barrier function. The inventors believe that such enhanced protective layer provides better and / or longer protection of the metal substrate. Here, a higher barrier function is defined as a higher impedance modulus (Ωcm) for the same frequency range (Hz). 2 ), specifically, a higher impedance modulus for frequencies of 10 Hz and 10 mHz as measured by EIS.
[0013] The coating compositions for use in the present invention are preferably chromium-free. By "chromium-free" is meant in particular the absence of any Cr compounds, such as Cr(VI) compounds, e.g. from chromates.
[0014] The coating composition for use in the present invention comprises a) a resin system comprising an organic film-forming resin and, optionally, a curing agent reactive with the organic film-forming resin. Within this specification, the term "film-forming resin" includes not only polymers but also monomers or oligomers that form a polymer system during curing of the coating. By organic film-forming resin, it is meant that the polymer, monomer or oligomer is organic (carbon-containing compound). The coating composition is preferably free of polysiloxanes. The coating composition is preferably not a sol-gel composition.
[0015] The film-forming resin may be selected, for example, from epoxy resins, hydroxy-functional resins (such as polyesters and poly(meth)acrylates), resins with one or more blocked hydroxyl groups (such as acetals), oxazolidine resins, carboxylic acid-functional resins), polyacrylates, polyurethanes, polyethers, polyaspartic esters, (blocked) isocyanates, thiol-functional resins, amine-functional resins, amide-functional resins, imide-functional resins (e.g., maleimides), alkyd resins, resins containing at least one olefinically unsaturated bond, silane-containing resins, polysiloxane resins, acetoacetate resins, functional (curable) fluorinated resins, and mixtures and hybrids thereof.
[0016] Preferably, the film-forming resin is selected from the group consisting of epoxy resins and hydroxy-functional resins, such as hydroxy-functional poly(meth)acrylates or polyester polyols, and polyurethanes. Epoxy resins are epoxy-functional polymers with an epoxy equivalent weight greater than 1, usually about 2. The most commonly used epoxy resins are polyglycidyl ethers of cyclic polyols, such as bisphenol A, resorcinol, hydroquinone and catechol, or polyglycidyl ethers of polyols, such as 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,2-bis(hydroxymethyl)cyclohexane. The hydroxy-functional resins preferably have a hydroxy functionality of 2.1 to 3.5 and an equivalent weight of at least 200 g / mol, based on solids.
[0017] Epoxy resins and polyurethanes are preferred film-forming resins for use in the present invention.
[0018] The film-forming resin is preferably present in the coating composition for use in the present invention in an amount of from 1 to 99% by weight, more preferably from 10 to 90% by weight, and even more preferably from 20 to 80% by weight, based on the total weight of the non-volatile components of the coating composition.
[0019] In some embodiments, the coating composition may further contain a curing agent reactive with the film-forming resin. The curing agent contains a functional group reactive with the functional group of the resin. The type of curing agent depends on the nature of the film-forming resin. The curing agent suitable for a particular film-forming resin is common knowledge to those skilled in the art. For example, an acetoacetate resin-based coating composition preferably contains a ketimine-based curing agent.
[0020] The epoxy resin-containing composition preferably contains an aliphatic or aromatic amine curing agent, a polyamide curing agent, a thiol-based curing agent. Suitable epoxy resins are bisphenol A, bisphenol F, bisphenol A / F, novolac and aliphatic epoxy resins. Suitable amine curing agents are aliphatic amines and their adducts (e.g., Ancamine® 2021), phenalkamines, cycloaliphatic amines (e.g., Ancamine® 2196), amidoamines (e.g., Ancamide® 2426), polyamides and their adducts, and mixtures thereof. The epoxy / NH molar ratio in the epoxy amine-type coating composition is preferably in the range of 0.6 to 2.0, more preferably 0.8 to 1.7. For solvent-based epoxy amine coating compositions, the epoxy / NH molar ratio is preferably in the range of 0.6 to 1.4, more preferably 0.8 to 1.2, and most preferably 0.85 to 1.1. For aqueous coating compositions, the epoxy / NH molar ratio is preferably in the range of 0.6 to 2.0, more preferably 0.9 to 1.7, and most preferably 1.3 to 1.7.
[0021] Preferred curing agents for hydroxy-functional resins are isocyanates and isocyanurates. Suitable isocyanate curing agents include aliphatic, cycloaliphatic and aromatic polyisocyanates, such as trimethylene diisocyanate, 1,2-propylene diisocyanate, tetramethylene diisocyanate, 2,3-butylene diisocyanate, hexamethylene diisocyanate, octamethylene diisocyanate, 2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, dodecamethylene diisocyanate, α,α'-dipropyl ether diisocyanate, 1,3-cyclopentylene diisocyanate, 1,2-cyclohexylene diisocyanate, 1,4-cyclohexylene diisocyanate, 4-methyl-1,3-cyclohexylene diisocyanate, 4,4'-dicyclohexylene diisocyanate methane, 3,3'-dimethyl-4,4'-dimethyl ether diisocyanate, ... These polyisocyanates include cyclohexylene diisocyanate methane, m- and p-phenylene diisocyanate, 1,3- and 1,4-bis(isocyanatomethyl)benzene, 1,5-dimethyl-2,4-bis(isocyanatomethyl)benzene, 1,3,5-triisocyanatobenzene, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,4,6-toluene diisocyanate, α,α,α',α'-tetramethyl o-, m-, and p-xylylene diisocyanate, 4,4'-diphenylene diisocyanate methane, 4,4'-diphenylene diisocyanate, 3,3'-dichloro-4,4'-diphenylene diisocyanate, naphthalene-1,5-diisocyanate, isophorone diisocyanate, transvinylidene diisocyanate, and mixtures of the aforementioned polyisocyanates.
[0022] Adducts of polyisocyanates are also suitable curing agents, such as biurets, isocyanurates, allophonates, uretdiones, and mixtures thereof. Examples of such adducts are the adduct of two molecules of hexamethylene diisocyanate or isophorone diisocyanate to a diol, for example ethylene glycol, the reaction product of three molecules of hexamethylene diisocyanate with one molecule of water, the adduct of one molecule of trimethylolpropane to three molecules of isophorone diisocyanate, the adduct of one molecule of pentaerythritol to four molecules of toluene diisocyanate, the isocyanurate of hexamethylene diisocyanate (Desmodur® N3390, formerly Bayer), the uretdione of hexamethylene diisocyanate (Desmodur® N3400, formerly Bayer), the allophonate of hexamethylene diisocyanate (Desmodur® LS 2101, formerly Bayer), and the isocyanurate of isophorone diisocyanate (Vestanate® T1890, formerly Huels). Furthermore, (co)polymers of isocyanate-functional monomers are suitable for use, such as α,α′-dimethyl-m-isopropenyl benzyl isocyanate. Finally, the abovementioned isocyanates and their adducts may also be present in the form of blocked or latent isocyanates.
[0023] In one preferred embodiment, the film-forming resin is a hydroxyl-functional resin and the curing agent comprises isocyanate functionality, hi another preferred embodiment, the film-forming resin comprises epoxy functionality and the curing agent comprises amine functionality.
[0024] The coating composition may be a one-component or two-component (2K) composition, or a composition having three or more components. Preferably, the composition is a 2K composition. A 2K coating composition consists of two components that are stored separately and mixed immediately before application to a substrate. Typically, the first component contains an organic film-forming resin and the second component contains a hardener.
[0025] The coating compositions for use in the present invention include a lithium salt that has limited solubility in water.
[0026] The lithium salt has a solubility in water of at least 0.01, preferably 0.05, more preferably at least 0.1 g / L, measured in water at 20°C. Lithium salts with a solubility of at least 0.5, more preferably at least 1, even more preferably at least 5 g / L show particularly good results. Lithium salts with a solubility of less than 0.01 g / L do not show sufficient activity. The solubility of the lithium salt is less than 120 g / L, preferably less than 100 g / L, more preferably less than 85 g / L. Too high a solubility can lead to problems in the formulation of the coating composition, for example a non-uniform coating composition, which can lead to problems in application. The lithium salt has a solubility in the range of 0.01 to 120 g / L, measured in water at 20°C. The solubility is preferably in the range of 1 to 100 g / L. The solubility in water is measured according to OECD Guideline No. 105, EU method A.6 (flask method, procedure §23), which describes the preparation of a saturated solution, after which the concentration in the solution is measured by a suitable analytical method. Suitable analytical methods for determining the concentration of the relevant ions are known to the skilled person and can be selected depending on the ion. In particular, for lithium salts, the inductively coupled plasma mass spectrometry (ICP-OES) method is used.
[0027] The lithium salt is selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate. References herein to phosphates are references to orthophosphates unless otherwise indicated. The solubility of lithium carbonate in water is 13 g / L, lithium phosphate 0.39 g / L, lithium oxalate 62 g / L, and lithium tetraborate 28 g / L, all at 20° C. Preferably, the lithium salt is selected from the group consisting of lithium carbonate, lithium phosphate, lithium oxalate, and any mixture of two or more thereof. In some embodiments, lithium carbonate is the preferred salt. It can be used alone or in mixture with other lithium salts, such as lithium carbonate and lithium phosphate. In other embodiments, lithium phosphate may be preferred.
[0028] The coating composition preferably does not include lithium salts having a solubility of less than 0.01 g / L at 20° C. In another embodiment, the coating composition preferably does not include lithium salts having a solubility in water of more than 120 g / L at 20° C., such as lithium chloride or lithium nitrate. Preferably, the coating composition does not include any lithium salts other than lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate.
[0029] For best results, the lithium salt selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate is preferably present in the coating composition in an amount of at least 1.3 wt.%, more preferably at least 1.6 wt.%, even more preferably at least 2 wt.%, more preferably at least 2.5 wt.%, even more preferably at least 3 wt.% lithium based on the solids weight of the resin system. "Solids weight of resin system" refers to the total dry weight of the resin system, i.e., all film-forming resins in the coating composition, and the hardener, if present. The amount of lithium salt selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate in the coating is such that the weight of lithium is preferably in the range of 1.3 to 40 wt.%, based on the solids weight of the resin system. The coating composition preferably does not contain more than 40 wt.%, or more than 30 wt.%, or more than 25 wt.%, or more than 20 wt.%, or more than 15 wt.%, or more than 10 wt.% lithium based on the solids weight of the resin system. Below 1.3 wt% lithium, the protective layer may not be sufficiently strengthened, especially when lithium carbonate is used as the lithium salt. At the upper limit, it may not be practical to include more lithium in the composition due to cost and because the effect is already achieved at low concentrations. When the lithium salt is lithium phosphate, the lithium phosphate is preferably present in an amount of at least 2.0 wt%, more preferably at least 3.0 wt%, even more preferably at least 4.0 wt%, and even more preferably at least 5.0 wt% lithium, based on the weight of the solids of the resin system.
[0030] The coating composition further comprises a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD). The zinc salt of DMTD may be present by itself or as part of a hybrid compound. References herein to hybrid compounds (sometimes referred to as hybrid pigments) are inseparable intimate blends of two or more solid compounds, including both organic and inorganic compounds, typically formed by coprecipitation. Examples of hybrid compounds include host-guest compounds, where the host matrix is inorganic and has a layered structure, and the guest compound is organic. However, in some embodiments, it may be preferred that the zinc salt of DMTD does not form part of the hybrid pigment.
[0031] The zinc salt of DMTD is 2,5-dimercapto-1,3,4 thiadiazole zinc salt (VII) (CAS 63813-27-4), which is a 1:2 salt of Zn and DMTD. The reference "1:2 salt" herein means that it is formed from 1 mole of Zn and 2 moles of DMTD. The salt is further referred to herein as Zn(DMTD) 2 or "zinc salt of DMTD". The zinc salt of DMTD can be obtained by known methods, for example by reacting ZnO with DMTD as described in Example 1 of WO 02 / 092880. The zinc salt of DMTD is commercially available, for example as part of Inhibicor 1000 from WPC Technologies. Zn(DMTD) 2 The water solubility of is reported to be 0.4 g / L at 24 °C.
[0032] In some embodiments, the zinc salt of DMTD is zinc oxide and / or a zinc salt, such as zinc orthophosphate or zinc cyanamide (CH 2 N 2In some embodiments, the coating composition is free of ZnO. In some embodiments, the coating composition is free of zinc orthophosphate. In yet other embodiments, the coating composition is free of zinc cyanamide. In some embodiments, the composition is free of ZnO, zinc orthophosphate, and zinc cyanamide. Without wishing to be bound by any theory, it is believed that Zn(DMTD) 2 Only Zn is believed to serve to enhance the barrier properties of the protective layer formed by the lithium ions in the lithium salt, and therefore the presence of other Zn compounds is not necessary.
[0033] However, in other embodiments, it may be beneficial for the coating composition to include an additional zinc-containing compound, such as ZnO, zinc orthophosphate, zinc cyanamide, or any combination thereof. An example of a combination is Zn(DMTD) 2 and ZnO, or Zn(DMTD) 2 and zinc orthophosphate, or Zn(DMTD) 2 and zinc cyanamide. Zn(DMTD) 2 When present in combination with a further zinc compound, Zn(DMTD) 2 The amount is 1 to 99% by weight, preferably 10 to 98% by weight, more preferably 20 to 95% by weight, and most preferably 30 to 90% by weight, based on the total weight of the zinc compound.
[0034] In some embodiments, Zn(DMTD) in a mixture with other zinc compounds 2The content of may be 50% by weight, preferably more than 60% by weight, more preferably more than 70% by weight, most preferably more than 80% by weight, more preferably more than 90% by weight, based on the solids weight of the mixture. An example of a suitable mixture is 1-30% by weight of Zn orthophosphate, 1-20% by weight of ZnO, and at least 50% by weight, for example 50-98% by weight of Zn(DMTD) based on the solids weight of the mixture. 2 Zn(DMTD) in the Zn compound mixture 2 Much lower levels may result in insufficient protection, especially when the DMTD content in the coating composition is less than 0.05 wt. % based on the weight of solids in the resin system.
[0035] In some embodiments, Zn(DTMD) 2 is present in combination with other zinc compounds, such as ZnO, zinc orthophosphate, zinc cyanamide, or any combination thereof, and Zn(DTMD) in the aforementioned mixture 2 is greater than 50 wt.-%, preferably greater than 60 wt.-%, more preferably greater than 80 wt.-%, and most preferably greater than 90 wt.-%, based on the solids weight of the mixture, and the DMTD content in the coating composition is at least 0.05 wt.-%, preferably at least 1 wt.-%, and more preferably at least 2 wt.-%, based on the solids weight of the resin system.
[0036] Preferably, the zinc salt of DMTD is present in the coating composition to provide at least 0.05 wt% DMTD, more preferably at least 0.1 wt%, even more preferably at least 0.4 wt%, or at least 0.6 wt%, or at least 1 wt%, more preferably at least 2 wt% or at least 4 wt% DMTD based on the solids weight of the resin system. Preferably, the amount is less than 50 wt%, or less than 40 wt%, or less than 30 wt%, or less than 20 wt% DMTD based on the solids weight of the resin system. When used in an amount less than 0.05 wt%, the synergy with lithium is believed to be too low to actually provide any benefit. Using an amount greater than 50 wt% is believed to be impractical, for example, due to potential formulation problems or high cost.
[0037] The coating composition preferably contains the lithium salt and the zinc salt of DMTD in an amount such that the weight ratio of lithium to DMTD, calculated as the weight ratio of the lithium content to the DMTD content, is 0.01 to 20, preferably 0.1 to 10. In some embodiments, it may be preferred that the content of DMTD (present as the zinc salt of DMTD) is equal to or greater than the content of lithium (present as the lithium salt). In other embodiments, it may be preferred that the content of DMTD (present as the zinc salt of DMTD) is equal to or less than the content of lithium (present as the lithium salt).
[0038] As discovered by the inventors and demonstrated in the Examples, the combination of a lithium salt in an organic coating with a zinc salt of DMTD shows an unexpected enhancement of the barrier properties of the protective layer formed on an exposed metal substrate. The protective layer is formed at locations where coating defects occur, which in the Examples are simulated by a scribe that penetrates the coating and exposes the bare metal to the environment. Unlike other known corrosion inhibitors, lithium salts are known to form an irreversible protective layer on metal substrates (e.g., aluminum alloys) via a mechanism of leaching from the coating matrix. The protective layer provides a barrier between the metal substrate and the environment. The barrier function of this layer is not visible to the naked eye, but can be measured using electrochemical impedance spectroscopy (EIS). In the coating composition, Zn(DMTD) is used in combination with a lithium salt and an organic film-forming resin. 2 The presence of Zn(DMTD) results in a much higher impedance value for the protective layer than when only the lithium salt is used or when the lithium salt is used together with the other screened potentially active compounds. A higher impedance value means that the protective layer has a higher barrier function or is "enhanced". An enhanced protective layer can provide improved or longer term protection. This enhancement of the protective layer can be achieved by the addition of Zn(DMTD) as supported by the following examples. 2 This is unexpected since it does not exhibit barrier properties or protective layer formation per se.
[0039] The coating composition may further comprise at least one magnesium compound. Suitable magnesium compounds are magnesium-containing materials, such as magnesium metal, magnesium oxide, magnesium oxyaminophosphate salts (e.g., Pigmentan® 465M), magnesium carbonate, and magnesium hydroxide. Magnesium metal is preferably used in the form of particles, such as powder, flakes, spheres, or spheroids. It should be noted that magnesium metal and magnesium metal alloy particles require specific stabilizers when used in aqueous coating compositions. Such stabilizers are generally known and commercially available. Preferably, magnesium oxide is used as the magnesium compound.
[0040] The magnesium compound is preferably present in the coating composition in an amount of 0.1 to 50% by weight, more preferably 1 to 35% by weight, and most preferably 5 to 20% by weight, based on the dry weight of the coating composition (the sum of the weights of the non-volatile components of the coating composition).
[0041] The magnesium oxide or magnesium salt is preferably present in an amount such that the weight ratio of Mg:Li is at least 0.1:1, more preferably at least 0.5:1, even more preferably at least 1:1, and even more preferably at least 3:1. This ratio is preferably less than 30:1, more preferably less than 25:1, even more preferably less than 15:1, and even more preferably less than 10:1, and most preferably less than 8:1.
[0042] When magnesium metal or alloy is present in the composition according to the invention, the weight ratio Mg:Li is preferably less than 500:1, more preferably less than 300:1, even more preferably less than 250:1, even more preferably less than 100:1, even more preferably less than 50:1 and most preferably less than 25:1.
[0043] Preferably, the composition contains a combination of the lithium salt, magnesium oxide, and zinc salt of DMTD described above, preferably in a weight ratio of (1-5):(1-2):1, preferably about 3:1.5:1, for the lithium salt, magnesium oxide, and zinc salt of DMTD, respectively.
[0044] In some embodiments, the coating composition further comprises one or more additional corrosion inhibitors. The additional corrosion inhibitors can be organic or inorganic. Examples of inorganic inhibitors are phosphates, such as zinc orthophosphate, zinc orthophosphate hydrate, zinc aluminum orthophosphate; polyphosphates, such as strontium aluminum polyphosphate hydrate, zinc aluminum polyphosphate hydrate, magnesium aluminum polyphosphate, zinc aluminum triphosphate, and magnesium aluminum triphosphate. Inhibitors further include metal oxides, such as oxides of zinc, magnesium, aluminum, lithium, molybdate, strontium, cerium, and mixtures thereof: metals such as Zn metal, Mg metal, and Mg alloys. Examples of organic inhibitors are thiol compounds and azoles, such as imidazoles, thiazoles, tetrazoles, triazoles, such as (substituted) benzotriazoles, and 2-mercaptobenzothiazole.
[0045] In some embodiments, the additional corrosion inhibitor is a thiol compound other than 2,5-dimercapto-1,3,4-thiadiazole zinc salt (VII) or an azole. An azole is a five-membered N-heterocyclic compound that contains a nitrogen atom and at least one other non-carbon atom (i.e., nitrogen, sulfur, or oxygen) as part of the ring. Examples of suitable compounds include 5-methylbenzotriazole and 2-mercaptobenzothiazole (2-MBT). Preferably, 2-MBT is present as the additional corrosion inhibitor.
[0046] Other compounds which may be present in coating compositions for use in the present invention are colour pigments (e.g. titanium dioxide or yellow iron oxide), extenders (e.g. talcum, barium sulfate, mica, calcium carbonate, silica, or wollastonite), rheology modifiers (e.g. Bentone SD 2 or organic rheology modifiers), flow and levelling agents (e.g. polysiloxane and polyacrylate levelling additives), and solvents (e.g. ketones such as methyl isobutyl ketone, aromatics such as xylene, alcohols such as benzyl alcohol, esters such as butyl acetate, and aliphatic solvents).
[0047] In a preferred embodiment, the coating composition for use in the present invention is a liquid coating composition. The composition may include a volatile liquid diluent, such as a volatile organic solvent or water. The composition may be water-based, solvent-based, or solvent-free. The term "solvent-free" is defined as including a total content of volatile liquid diluent of less than 5% by weight, including water and organic solvent. The term "water-based" is defined as including at least 50% by weight of water of the total weight of the volatile liquid diluent (including both water and organic solvent). The term "solvent-based" is defined as including an organic solvent in an amount of at least 50% by weight of the total weight of the volatile liquid diluent (including both water and organic solvent). The coating composition is preferably solvent-based.
[0048] In some embodiments, the coating composition can be substantially free of water (non-aqueous), meaning that the water content is less than 1% by weight, preferably less than 0.1% by weight, based on the total weight of the coating composition. More preferably, the coating composition is completely free of water.
[0049] The coating compositions for use in the present invention are preferably low temperature curable compositions, meaning that they are curable, i.e. capable of forming a network, at temperatures below 120° C., preferably below 100° C., more preferably below 80° C., even more preferably below 50° C., and most preferably at ambient conditions. In other embodiments, the coating compositions may be high temperature curable compositions, for example curable at temperatures of 120° C. or higher, preferably 140° C. or higher.
[0050] The non-volatile content of the coating composition is preferably 10 to 95% by weight, more preferably 25 to 75% by weight, and even more preferably 30 to 70% by weight. In the case of an aqueous coating composition, the non-volatile content is preferably in the range of 30 to 60% by weight.
[0051] The volatile organic content (VOC) of the coating composition (measured according to ASTM D3960) is preferably less than 700 g / L, such as less than 500 g / L, more preferably less than 300 g / L.
[0052] The coating composition according to the present invention can be used as an anticorrosive primer for coating non-ferrous metal substrates, such as magnesium, magnesium alloy, titanium, aluminum, aluminum alloy, and lithium-aluminum alloy substrates.Preferred non-ferrous metal substrates are aluminum alloys.Examples of suitable aluminum alloys are 2024-T3 (bare or clad), 7075-T6 (bare or clad), 2098, 2099, 2198, 6061, 6111, 6022, 5052, 5083, 5251, 5454, 7475, 7017, and 7020.
[0053] The coating composition for use in the present invention is also suitable for coating iron substrates. Examples of suitable iron substrates are cold and hot rolled steel, stainless steel 304, B952 (zinc phosphate modified), B1000 (iron phosphate modified), and zinc modified steels such as EZG 60G, EZG 60G with zinc phosphate modified, G90, and Galvanneal HIA Zn / Fe A45.
[0054] The coating compositions for use in the present invention can be used as primers, bonding primers, self-priming topcoats, intermediate coats and / or topcoats. They can also be used in coating systems in which at least two layers have the compositions described in this disclosure.
[0055] The coating compositions can be applied to substrates with or without the use of a hexavalent chromium-free pretreatment, such as a sol-gel system such as AC-® 131 (AC Tech), PreKote® (Pantheon Chemical), or a conversion treatment.
[0056] The coating composition may also be applied to anodized surfaces, such as chromate anodized (CAA) surfaces, tartaric acid sulfuric acid anodized (TSA) surfaces, sulfuric acid anodized (SAA) surfaces, phosphoric acid anodized (PAA) surfaces, phosphoric acid sulfuric acid anodized (PSA) surfaces, and borosulfuric acid anodized (BSAA) surfaces.
[0057] The coating composition can be advantageously used as a primer coating for non-ferrous metal substrates. It can be applied as a single layer or multiple layers. In a preferred embodiment, the coating composition is applied to the substrate to form at least one primer layer in a multi-layer coating system. The topcoat layer applied over the primer layer can be a clearcoat or a pigmented topcoat. Alternatively, the coating system can also include a color and / or effect-imparting basecoat applied over the primer layer and a clearcoat applied over the basecoat. The composition can also be used as a topcoat, the topcoat being either clear or pigmented.
[0058] The composition for use in the present invention can be used in a multi-layer coating system comprising at least one layer obtained from the coating composition according to the first aspect of the present invention, i.e. comprising a resin system a), a lithium salt b) and a zinc salt of DMTD. After application, components a), b) and the zinc salt of DMTD are present in a single layer. Preferably, the layer formed from the coating composition is used as a primer layer applied to a substrate, which is optionally pretreated. The topcoat may be a clearcoat or a pigmented topcoat, or the clearcoat is applied over the basecoat layer, if the topcoat comprises a color- and / or effect-imparting basecoat applied over the primer layer.
[0059] It has been found that the enhancing effect on the barrier function, as measured by EIS, of the protective layer formed on the surface of the exposed portion of the coated metal substrate (coated with a coating composition comprising a lithium salt and an organic film-forming resin as described above) is synergistic, meaning that the effect is much higher than would be expected based on the individual components, in particular, preferably at least two times higher, more preferably at least three times higher than the effect of the individual components (in this case the lithium salt and the zinc salt of DMTD).
[0060] The coating composition for use in the present invention is particularly suitable for coating metal substrates. The metal substrate may be a non-ferrous metal substrate, such as aluminum or an aluminum alloy. Alternatively, the metal substrate may be a ferrous metal substrate. The substrate may be intended for external or internal use. Examples include aircraft structural parts, aircraft cabin parts or vehicles. The coating composition is particularly suitable for use in the aerospace, automotive or coil coating industries. EXAMPLES
[0061] Chemicals used Lithium carbonate-ACS reagent, ≥99.0%, Sigma Aldrich
[0062] Desmophen 650 MPA - a branched hydroxyl-bearing polyester from Covestro AG, 65% by weight in 1-methoxypropyl acetate-2 (MPA), 5.3% OH content
[0063] Tioxide TR 92 - Titanium dioxide from Huntsman
[0064] Zn(DMTD) 2 - Prepared according to Example 1 of WO 02 / 092880 A1
[0065] Hybrid 1-45 wt% Zn(DMTD) 2 , 32% by weight of Zn 3 (PO 4 ) 2 .H 2 0, a hybrid pigment prepared according to Example 2 of WO 02 / 092880 A1 containing 23 wt. % ZnO (wt. % based on the total weight of the mixture)
[0066] Disodium salt of hybrid 2-DMTD (Na 2 Zn(DMTD) neutralized with Zn(DMTD) 2 Contains neutralized salt of Zn (DMTD) with an estimated content of 97% by weight 2A hybrid pigment prepared according to Example 1 of WO 2008 / 140648(A9)
[0067] Hybrid 3 - prepared as Hybrid 1 but with 75 wt. % Zn(DMTD) 2 , 14% by weight of Zn 3 (PO 4 ) 2 .H 2 O, a hybrid pigment containing 11 wt. % ZnO (wt. % based on the total weight of the mixture)
[0068] Hybrid 4 - prepared as Hybrid 1 but with 15 wt. % Zn(DMTD) 2 , 49% by weight of Zn 3 (PO 4 ) 2 .H 2 O, a hybrid pigment containing 36 wt. % ZnO (wt. % based on the total weight of the mixture)
[0069] Hybrid 5 - prepared as Hybrid 1 but with 0 wt% Zn(DMTD) 2 , 58% by weight of Zn 3 (PO 4 ) 2 .H 2 O, 42 wt.% ZnO (wt.% based on the total weight of the mixture) Hybrid 6 - prepared as Hybrid 1 but without phosphate and 75 wt.% Zn(DMTD) 2 and 25 wt. % ZnO (wt. % based on the total weight of the mixture).
[0070] Hybrid 7 - prepared as Hybrid 1 but without phosphate and with 45 wt% Zn(DMTD) 2 and 55 wt. % ZnO (wt. % based on the total weight of the mixture).
[0071] Hybrid 8 - prepared as Hybrid 1 but without phosphate and with 15 wt% Zn(DMTD) 2and 85 wt. % ZnO (wt. % based on the total weight of the mixture).
[0072] Hybrid 9 - prepared as Hybrid 1 but without phosphate and with 7 wt% Zn(DMTD) 2 and 93 wt. % ZnO (wt. % based on the total weight of the mixture).
[0073] Airwhite AW 15 - Barium Sulfate from Sibelco Specialty Minerals
[0074] Desmodur N-75 MPA / X-Aliphatic polyisocyanate resin based on hexamethylene diisocyanate (HDI), dissolved in n-butyl acetate and xylene (1:1) from Covestro AG, solids content 75% by weight, NCO content 16.5%
[0075] Silquest A-187 - an epoxy-functional silane from Momentive Performance Materials
[0076] Electrochemical Impedance Spectroscopy (EIS) The barrier properties of the protective layer in the defect area were quantified and evaluated using electrochemical impedance spectroscopy (EIS) as described in Non-Patent Document 1: Visser, P., Liu, Y., Terryn, H. et al. “Lithium salts as leachable corrosion inhibitors and potential replacement for hexavalent chromium in organic coatings for the protection of aluminum alloys” J Coat Technol Res 13, 557-566 (2016)
[0077] EIS measurements were performed at open circuit potential (OCP) using a computer-controlled potentiostat over a frequency range of 0.01 Hz to 30,000 Hz, measuring seven points during a tenfold increase in frequency, applying a sinusoidal amplitude of 10 mV. Measurements were performed using a three-electrode configuration in a Faraday cage with a saturated calomel electrode (SCE) as the reference electrode, platinum gauze as the counter electrode, and a scribe panel as the working electrode, using 0.05 M NaCl electrolyte. The area exposed to the electrolyte was 12.5 cm. 2 and the effective bare electrode (i.e., coating defect) area is 0.48 cm 2 and the volume of the electrolyte is 60 cm 3 Measurements were recorded after 2 hours of exposure to 0.05 M NaCl electrolyte for at least three samples.
[0078] The results of the examples are presented in the form of a table with Zmod values at 10 mHz and 10 Hz. The higher the impedance value, the stronger the protective layer.
[0079] Preparation of test panels Unless otherwise stated, the test panels are AA2024-T3 bare aluminum alloy, typically 7.0 cm by 7 cm (3 by 6 in) and 0.8 mm thick, anodized in tartaric sulfuric acid (TSA) in accordance with aerospace requirements (AIPI 02-01-003).
[0080] The ingredients of Component A were added sequentially to a 370 ml glass jar with stirring. Then, 400 grams of Zirconox pearls (1.7-2.4 mm) were added to the mixture for grinding and dispersion of the pigment. The sample was shaken for 20 minutes in a Skandex paint shaker to achieve a grinding degree of less than 25 μm. After shaking, the pearls were separated from the coating. Component B was prepared separately by mixing.
[0081] Component B is added to component A under stirring to ensure sufficient mixing to obtain a homogenous sample. After mixing of the separate components, the coating is allowed to induce for 30 minutes.
[0082] The coatings were applied at ambient conditions (23°C, 55% RH) using a high volume, low pressure (HVLP) spray gun. After coating and a 1-hour flash-off period, the coated panels were cured at 80°C for 1 hour and dried under ambient conditions for 7 days. The dry film thickness of the coating after drying was 20-25 μm. The coated panels were scribed (cross scribe 2 cm x 2 cm) using a mechanical milling device, leaving a U-shaped scribe (cross scribe 2 cm x 2 cm) with a width of 1 mm and a depth of 100-150 μm. After scribing, the samples were exposed to a neutral salt spray test (ASTM-B117) for 168 hours.
[0083] Example 1: Li salt and Zn(DTMD) 2 Synergy with Formulations 1-1 to 1-4 were prepared using the components listed in Table 1. The component contents are given in parts by weight (g), and the contents of the active components Li and DMTD are given as weight % based on the resin system solids.
[0084] The ingredients of Component A were added sequentially to a 370 ml glass jar with stirring. Then, 400 grams of Zirconox pearls (1.7-2.4 mm) were added to the mixture for grinding and dispersion of the pigment. The sample was shaken for 20 minutes in a Skandex paint shaker to achieve a grinding degree of less than 25 μm. After shaking, the pearls were separated from the coating. Component B was prepared separately by mixing.
[0085] Component B was added to Component A under stirring to ensure sufficient mixing to obtain a homogenous sample. After mixing of the separate components, the coating was allowed to induce for 30 minutes.
[0086] [Table 1]
[0087] Formulations 1-1, 1-2, and 1-3 are comparative formulations, and formulation 1-4 is in accordance with the present invention. The results of the EIS measurements are shown in FIG.
[0088] Zn(DMTD) 2 The coating containing both Zn(DMTD) and Li salts (1-4) was compared with the active ingredient-free formulation (1-1) or Zn(DMTD) 2 It can be seen that the formulation containing only Li salt (1-2) or only Li salt (1-3) exhibits a significantly higher impedance |Z| (also called "Zmod") value.
[0089] This effect was observed in the Li salts (1-3) and Zn(DMTD). 2 This is much stronger than the sum of the individual effects of (1-2) and is therefore a synergistic effect.
[0090] This result also indicates that Zn(DMTD) 2 This indicates that coating 1-2 alone does not affect the formation of a protective layer in the defect area. In particular, coating 1-2 has a low impedance value comparable to that of no coating (negative reference) (1-1).
[0091] Example 2: Comparison with other azoles Formulations 2-1 through 2-7 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 2. The ingredient contents are given in parts by weight (g). The active ingredient contents are also given as weight % based on the resin system solids. The molar amount of the azole is the same across all formulations in this example. BTA is benzotriazole and 2-MBT is 2-mercaptobenzothiazole.
[0092] [Table 2]
[0093] Formulations 2-1, 2-2, 2-3, 2-4, 2-5, 2-6 are comparative formulations and formulation 2-7 is in accordance with the present invention. The results of the EIS measurements are shown in FIG.
[0094] The results also showed that the combination of Li salts with other azoles (BTA or 2-MBT) was superior to that of Zn(DMTD). 2 This shows that the combination of Li salt and Zn(DMTD) does not have the same synergistic effect as the combination of Li salt and Zn(DMTD). 2 The combination with provides a much higher impedance value associated with an enhanced protective layer in the defect area.
[0095] Example 3: Zn(DMTD) in hybrid pigments 2 Formulations 3-1 through 3-7 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 3. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.
[0096] [Table 3]
[0097] Formulations 3-1, 3-2, 3-3 and 3-4 are comparative formulations, while formulations 3-5, 3-6 and 3-7 are in accordance with the present invention. The results of the EIS measurements are listed in Table 3.
[0098] This result is consistent with that of Zn(DMTD) 2 When incorporated into hybrid pigments, Zn(DMTD) used as a pure component 2 The results show that the same effect is observed with lithium salts as with Zn(DMTD) in the coating in all formulations. 2 The total amount is the same.
[0099] Example 4: Zn(DMTD) in hybrid pigments 2 Different ratios of Formulations 4-1 through 4-7 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 4. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.
[0100] [Table 4]
[0101] Formulations 4-1, 4-2 and 4-6 are comparative formulations, while formulations 4-3, 4-4, 4-5 and 4-7 are in accordance with the invention. The results of the EIS measurements are listed in Table 4.
[0102] In these examples, Zn(DMTD) in the hybrid pigment 2 The weight ratio of Zn(DMTD) in the coating varies from low to high. 2 The amount of Zn(DMTD) is the same. 2 All examples using hybrid pigments containing ZnO show a strengthening effect of the protective layer in the defective area. There is little difference in the strengthening of the different hybrid pigments. Therefore, this effect is not observed when using ZnO or Zn 3 (PO 4 ) 2 The presence and amount of
[0103] Example 5: Alternative hybrid pigments; ZnO and Zn(DMTD) 2 Combination with Formulations 5-1 through 5-7 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 5. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.
[0104] [Table 5]
[0105] Formulations 5-1 and 5-2 are comparative formulations, the other formulations are according to the invention. The results of the EIS measurements are listed in Table 5.
[0106] In these examples, the Li salt is Zn(DMTD) 2 and combined with hybrid pigments based solely on ZnO. Zn(DMTD) 2The amount of Li and Zn(DTMD) is the same in all examples, and all samples show the same effect of strengthening the protective layer. 2 It can be concluded that the synergistic effect of Li salt and Zn(DMTD) is not affected. 2 This is due to a combination of.
[0107] Example 6: Alternative hybrid pigments; ZnO and Zn 3 (PO 4 ) 2 Combination with Formulations 6-1 through 6-5 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 6. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.
[0108] In these experiments, Zn(DTMD) 2 ZnO and Zn with and without 3 (PO 4 ) 2 The performance of alternative hybrid pigments including
[0109] [Table 6]
[0110] Formulations 6-1, 6-2 and 6-3 are comparative formulations, the other formulations are according to the invention. The results of the EIS measurements are listed in Table 6.
[0111] ZnO and Zn 3 (PO 4 ) 2 It can be concluded that the combination of the hybrid pigment with Li salt has no synergistic effect on the barrier effect of the protective layer. 2 Only the presence of provides the effect according to the invention.
[0112] Example 7: Effect of ZnO Formulations 7-1 to 7-6 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 7. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.
[0113] These experiments examine the effect of ZnO. Examples include Li salts and / or Zn(DTMD) 2 They are used in the form of a physical mixture, not as part of a hybrid pigment.
[0114] [Table 7]
[0115] Formulations 7-1, 7-2, 7-3 and 7-4 are comparative formulations, the other formulations are according to the invention. The results of the EIS measurements are listed in Table 7.
[0116] As can be seen from the EIS results, ZnO alone does not show any synergistic effect with the Li salt. From this example, it is necessary to use Zn(DMTD) to have a strengthening effect on the protective layer. 2 It can be concluded that is necessary.
[0117] Example 8: Zn 3 (PO 4 ) 2 Effect Formulations 8-1 through 8-6 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 8. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.
[0118] In these experiments, the exemplary formulation was Zn 3 (PO 4 ) 2 , with or without Li and Zn(DTMD) 2 They are used in the form of a physical mixture, not as part of a hybrid pigment.
[0119] [Table 8]
[0120] Formulations 8-1, 8-2, 8-3 and 8-4 are comparative formulations, while 8-5 and 8-6 are according to the invention. The results of the EIS measurements are listed in Table 8.
[0121] As can be seen from these results, the formation of a protective layer in the defect area is important. 3 (PO 4 ) 2 No strengthening effect was observed when used alone with Li salt. Zn(DMTD) in the formulation containing Li salt 2 The addition of is necessary to have a synergistic enhancing effect on the barrier properties of the protective layer.
[0122] Example 9: ZnO and Zn 3 (PO 4 ) 2 Combination with Formulations 9-1 to 9-6 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 9. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.
[0123] In these experiments, the coating composition consisted of ZnO and Zn 3 (PO 4 ) 2 , with or without Li, and Zn (DTMD) 2 Contains Zn. 3 (PO 4 ) 2 The ratio of ZnO to ZnO is the same as in Hybrid 1, but is used in the form of a physical mixture rather than as part of a hybrid pigment.
[0124] [Table 9]
[0125] Formulations 9-1, 9-2, 9-3 and 9-4 are comparative formulations, while 9-5 and 9-6 are according to the invention. The results of the EIS measurements are listed in Table 9.
[0126] As can be seen from these results, ZnO and Zn 3 (PO 4 ) 2 The combination with Zn(DMTD) does not show any strengthening effect with Li salts. To obtain the strengthening effect of the protective layer in the defect area, Zn(DMTD) 2 The addition of
[0127] Example 10: Li salts of different concentrations Formulations 10-1 to 10-8 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 10. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.
[0128] In these experiments, the formulations were Li salts and Zn(DTMD) 2 with various concentrations of Li salt.
[0129] [Table 10]
[0130] Formulations 10-1, 10-2, 10-3, 10-4 and 10-5 are comparative formulations, the other formulations are according to the invention. The results of the EIS measurements are listed in Table 10.
[0131] Zn(DMTD) compared to a sample containing only the Li salt 2 It can be seen that significantly higher impedance values are obtained for compositions containing at least 1.3 wt. % Li relative to the resin system solids in combination with
[0132] Example 11: Different Concentrations of Zn(DMTD) 2 Formulations 11-1 to 11-8 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 11. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.
[0133] In these experiments, the active materials were Li salts and Zn(DTMD) 2 Including Zn(DTMD) 2 The concentrations vary.
[0134] [Table 11]
[0135] Formulations 11-1, 11-2 and 11-3 are comparative formulations, the other formulations are according to the invention. The results of the EIS measurements are listed in Table 11.
[0136] Zn(DTMD) 2 It can be concluded that even very small amounts of DMTD, such as 0.6 wt%, show a synergistic effect with any amount of Li salt. Even at these low concentrations of DMTD, there is a clear improvement (strengthening effect) of the barrier properties of the protective layer in the defect areas.
[0137] Example 12: Different Li salts (4.4% Li) Formulations 12-1 to 12-8 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 12. The amount of ingredients is given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.
[0138] In these experiments, the coatings contained different soluble Li salts, with a Li content of 4.4 wt. % based on the resin system solids. The lithium salts were chosen with different solubilities.
[0139] [Table 12]
[0140] Formulations 12-1 to 12-5 are comparative formulations, the other formulations are according to the invention. The results of the EIS measurements are listed in Table 12.
[0141] Zn(DTMD) 2 It can be concluded that the results show a strengthening effect with Li salts, whatever the salt used. The moderate effect on lithium phosphate is likely due to its low solubility in water.
[0142] Example 13: Different Li salts (1.3 wt% Li) Formulations 13-1 to 13-6 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 13. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.
[0143] In these experiments the coating composition contained different soluble Li salts with a Li content of 1.3 wt. % based on the resin system solids.
[0144] [Table 13]
[0145] Formulations 13-1 to 13-3 are comparative formulations, the other formulations are according to the invention. The results of the EIS measurements are listed in Table 13.
[0146] Zn(DTMD) 2 It can be concluded that most Li salts show an enhanced protective layer, even when used in amounts less than those in Example 12, except for lithium phosphate, for which better results were achieved with higher Li content (Example 12), which is likely due to its lower solubility in water.
[0147] Example 14: No Magnesium Oxide Formulations 14-1 to 14-4 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 14. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.
[0148] These experiments test whether the strengthening effect is also present in compositions that do not contain magnesium oxide.
[0149] [Table 14]
[0150] Formulations 14-1 through 14-3 are comparative formulations and 14-4 is in accordance with the present invention. The results of the EIS measurements are listed in Table 14.
[0151] The strengthening effect was also present in the absence of MgO and was observed purely with the lithium salt and Zn(DMTD). 2 It can be concluded that this is due to a combination of
[0152] Example 15: Lithium phosphate at different concentrations Formulations 15-1 to 15-6 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 15. The amounts of ingredients are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.
[0153] In these experiments, the concentration of lithium phosphate is varied so that the Li content of the resin-based solids is 2.0 to 7.0 wt.
[0154] [Table 15]
[0155] Formulations 15-1 to 15-3 are comparative formulations, and the other formulations are according to the invention. Test panels were prepared and scribed as described above. After scribing, the samples were exposed to a neutral salt spray test (ASTM-B117) for 96 hours. The results of the EIS measurements are listed in Table 15.
Claims
1. 1. Use of a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD), said zinc salt of DMTD being 2,5-dimercapto-1,3,4-thiadiazole zinc salt (VII), comprising a metal salt thereof and a) a resin system comprising an organic film-forming resin and optionally a curing agent reactive with said organic film-forming resin; b) a lithium salt having a solubility in water ranging from 0.01 to 120 g / L at 20° C. selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate; In a coating composition further comprising To enhance the barrier function of a protective layer produced as a result of the presence of said lithium salt in said coating composition when used on a metal substrate coated with said coating composition. Use of the zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD).
2. 2. The use according to claim 1, wherein the coating composition does not contain any zinc-containing compounds other than the zinc salt of DMTD.
3. 2. The use of claim 1, wherein the coating composition further comprises a zinc-containing compound selected from the group consisting of zinc oxide, zinc phosphate, zinc cyanamide, and any combination thereof.
4. 4. The use according to any one of claims 1 to 3, wherein the lithium salt is lithium carbonate.
5. 5. The use according to any one of claims 1 to 4, wherein the lithium salt is present in an amount of at least 1.3% by weight lithium based on resin system solids.
6. 5. Use according to any one of claims 1 to 4, wherein the lithium salt b) is lithium phosphate, said lithium phosphate being present in an amount of at least 2.0 wt.-%, preferably at least 3.0 wt.-%, more preferably at least 4.0 wt.-% lithium, based on resin system solids.
7. 7. Use according to any one of claims 1 to 6, wherein the zinc salt of DMTD is present in an amount of 0.05 to 20% by weight of DMTD based on resin system solids.
8. 8. The use according to any one of claims 1 to 7, wherein the film-forming resin is selected from the group consisting of epoxy resins, hydroxy-functional poly(meth)acrylates, polyester polyols and polyurethanes.
9. The use according to any one of claims 1 to 8, wherein the coating composition further comprises a thiol or an azole other than the 2,5-dimercapto-1,3,4-thiadiazole zinc salt (VII).
10. 10. Use according to any one of claims 1 to 9 in a multi-layer coating system on a metal substrate, said coating system comprising a layer obtained from the composition according to any one of claims 1 to 9.
11. 11. Use in a multi-layer coating system according to claim 10, wherein the layer obtained from the coating composition according to any one of claims 1 to 9 is a primer layer on said metal substrate.
Citation Information
Patent Citations
Multilayer and complex corrosion-resistant coating
JP2010520096A
Corrosion resistant adhesive sol-gel
JP2018154813A
Curable film-forming composition containing lithium silicate as a corrosion inhibitor and a metal substrate coated with multiple layers
JP2018524421A
Hybrid pigment grade corrosion inhibitor compositions and procedures
WO1999018044A1
Anti-corrosive coating composition
WO2010112605A1